The Cerebellum and Cognitive Function: Anatomical Evidence from a Transdiagnostic Sample - Bègue, Indrit; Elandaloussi, Yannis; Delavari, Farnaz; Cao, Hengyi; Moussa-Tooks, Alexandra; Roser, Mathilde; Coupé, Pierrick; Leboyer, Marion; Kaiser, Stefan; Houenou, Josselin; Brady, Roscoe; Laidi, Charles (Cerebellum (London, England), 2024)
Multiple lines of evidence across human functional, lesion, and animal data point to a cerebellar role, in particular of crus I, crus II, and lobule VIIB, in cognitive function. However, a mapping of distinct facets of cognitive function to cerebellar structure is missing. We analyzed structural neuroimaging data from the Healthy Brain Network (HBN). Cerebellar parcellation was performed with a validated automated segmentation pipeline (CERES) and stringent visual quality check ( n = 662 subjects retained from initial n = 1452). Canonical correlation analyses (CCA) examined regional gray matter volumetric (GMV) differences in association to cognitive function (quantified with NIH Toolbox Cognition domain, NIH-TB), accounting for psychopathology severity, age, sex, scan location, and intracranial volume. Multivariate CCA uncovered a significant correlation between two components entailing a latent cognitive canonical (NIH-TB subscales) and a brain canonical variate (cerebellar GMV and intracranial volume, ICV), surviving bootstrapping and permutation procedures. The components correspond to partly shared cerebellar-cognitive function relationship with a first map encompassing cognitive flexibility ( r = 0.89), speed of processing ( r = 0.65), and working memory ( r = 0.52) associated with regional GMV in crus II ( r = 0.57) and lobule X ( r = 0.59) and a second map including the crus I ( r = 0.49) and lobule VI ( r = 0.49) associated with working memory ( r = 0.51). We show evidence for a structural subspecialization of the cerebellum topography for cognitive function in a transdiagnostic sample.